Using Informational Technologies in the Training Process of Qualified Athletes - Yaroslav Svyshch; Olha Pavlos; Ruslan Pavlos; Alla Hohla; Tetyana Dukh (Lesya Ukrainka Volyn National University, 2018)
From year to year, the level of athlete's outcomes in different kinds of sports increases to an extremely high level. Taking into account this fact and the rapid development of information technologies in the world, there is an urgent problem of the review of modern computer programs and monitoring systems that can be used in sports, in particular in athletics. The purpose of our work was to analyze modern computer programs and monitoring systems that can be used in the training process of qualified athletes. The task of the work was to determine the peculiarities of the application of information and computer technologies in track and field athletics. The analysis of modern computer programs and monitoring systems in the field of physical culture and sports was carried out, their brief characteristics (Polar - «ProTrainer 5», Dartfish - «Dartfish Connect 5,5», Qualistys video computing complex, Fusion Smartspeed software package, Opto electronic system Opto-Gate (Jump), IMOOV three-dimensional evaluation system, SportKat 650TS simulator of stability and equilibrium, Quintic Biomechanics, Simi - Simi Matchix, Activio Sport monitoring system, Monokra 840E Monoker 840E, Myotest system). As a result of the task accomplished, modern computer technologies have been identified that provide real-time data on the functional state and the level of physical development of athletes, as well as the prevention of injuries and the preservation of health. The presented analysis of computer programs is used to obtain indicators of the level of development of physical qualities and the main characteristics of the technique of performing exercises through the use of a 3D optical-optical image. It has been established that modern research of sports equipment indicators is carried out using video-computer programs that analyze the athlete's movements. Individual computer programs use their capabilities to rehabilitate athletes.